Increment of patchouli alcohol in patchouli oil by vacuum distillation fraction method - Yuliani Aisyah; Sri Haryani Anwar; Yulia Annisa (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
The quality of Indonesian patchouli oil is commonly lower than that required by standard (substandard). The quality of patchouli oil is determined by the level of an organic compound known as patchouli alcohol (PA). This research is aimed to study the influence of the initial level of patchouli alcohol in patchouli oil to the final oil quality after being separated by vacuum distillation fraction method. The patchouli oils used had three different initial level of patchouli alcohol (31.11%, 32.83% and 33.61%). The results show that the increments of the initial level of patchouli alcohol tend to lower the final concentrations of this compound in the patchouli oil. The oil with 31.11% of initial patchouli alcohol contained 49.07% PA after distillation, the initial PA of 32.83% became 42.87% and the oil with the highest initial PA (33.61%) consisted only 32.85% PA in its final quality.